2011
DOI: 10.3354/meps09290
|View full text |Cite
|
Sign up to set email alerts
|

Change in tropical rocky shore communities due to an alien coral invasion

Abstract: To determine how benthic, tropical, rocky shore communities were affected by the invasive coral species Tubastraea coccinea and T. tagusensis, 8 sites were studied during 2 yr on rocky shores in the southwest Atlantic Ocean (Brazil) by using both fixed and random sampling techniques. Overall, mean cover of T. tagusensis was 0.7% and T. coccinea was 0.4%, (the eleventh and sixteenth most abundant taxa, respectively, throughout the sites). Forty-two major space occupying taxa were registered. In fixed quadrats t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 56 publications
(69 reference statements)
0
42
0
4
Order By: Relevance
“…Tubastraea spp. in Brazil are showing signs of expansion and disruption of native species (Lages et al 2011, Sampaio et al 2012. Populations of this species have nearly monopolized artificial hard-bottom substrata, such as offshore platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Tubastraea spp. in Brazil are showing signs of expansion and disruption of native species (Lages et al 2011, Sampaio et al 2012. Populations of this species have nearly monopolized artificial hard-bottom substrata, such as offshore platforms.…”
Section: Discussionmentioning
confidence: 99%
“…So far nothing is known about the anemone's impact on ecosystems, but if high population densities, as observed in the Kiel Fjord become the rule, we would expect an impact on biochemical fluxes of the benthic ecosystem. For example, dense polyp mats could significantly influence the native benthic hard bottom communities, which are commonly dominated by blue mussels, by competition for space and food with other epibionts (Lages et al 2011). Furthermore, little is known about the food spectrum of the animals: D. lineata feeds mainly on small crustaceans (Williams 1972), but according to Baker et al (2004) the anemone might also prey on larvae of economically important taxa such as blue mussels and oysters.…”
Section: Present Distribution Of the Invasive Sea Anemone D Lineatamentioning
confidence: 99%
“…However, the same study showed that its biodiversity is subjected to a number of human pressures, including the presence of marinas, harbors, ports and an oil terminal that contribute to high marine traffic including ships and oil platforms that are vectors of marine NIS. The shallow rocky reef communities in the region are dominated by the zoanthid Palythoa caribaeorum and algal turfs (Lages et al 2011).…”
Section: Study Areamentioning
confidence: 99%